From InGaN pyramids to micro-LEDs characterized by cathodoluminescence. (18th March 2021) - Gustafsson, Anders; BI, Zhaoxia; Samuelson, Lars
Abstract: We present a study of the optical properties of various steps in the process of fabricating micro light-emitting diodes ( μ -LEDs) based on quantum wells embedded in micron-sized InGaN platelets. In this study, we focus on structures for red emission, but the technology is equally suitable for the less technologically challenging blue and green emitting μ -LEDs. The starting point is growth of an InGaN pyramid with a sub-micron sized hexagonal base. The pyramid is flattened to create a flat top c-facet for the subsequent InGaN quantum well growth. We compare two approaches, reshaping of the pyramid by high-temperature annealing; and by chemical mechanical polishing. Their merits are discussed. The flattened platelets are used as templates to grow low-strain single quantum wells in both heterostructures and full LEDs including n- and p-barriers on either side of the quantum well. The structures are investigated in terms of homogeneity in peak energy position and intensity using hyperspectral cathodoluminescence imaging. We observe that the main contribution to inhomogeneity is the growth of the initial pyramid, that exhibits regular, facet driven variations in the In incorporation.